The reaction products of the 193 nm photolysis of vinyl bromide and vinyl chloride studied by time-resolved Fourier transform infrared emission spectroscopy. - Carvalho, A; Hancock, G; Saunders, M (2006)
Time-resolved Fourier transform infrared (TRFTIR) emission spectroscopy has been used to study the 193 nm photolysis of vinyl bromide (C(2)H(3)Br) and vinyl chloride (C(2)H(3)Cl). Time-resolved IR emission was analysed to obtain nascent vibrational state populations of two primary photolysis products: HBr (v = 1-7) and HCl (v = 1-6). In both cases the nascent vibrational state populations monotonically decrease with increasing v and are in excellent agreement with previously published data. Time-resolved populations were analysed to yield rate constants for vibrational relaxation of HBr (v = 1-3) and HCl (v = 1-4) by parent vinyl bromide and vinyl chloride, respectively. In both cases the rate constants were found to increase with increasing vibrational quantum number, in agreement with a single quantum de-excitation via vibrational to vibrational energy transfer. Butadiene (C(4)H(6)) was identified as a secondary product of the photolysis of both vinyl halides, and shown to be formed from the reaction of parent vinyl halide with the vinyl radical. The presence of a buffer gas was found to produce a strong emission feature centred at 2,200 cm(-1), the intensity of which was dependent on the pressure of the buffer gas used, and whose kinetics are indicative of a secondary reaction product. We propose that this emission is from the vibrational progression of the electronic transition A(0, v, 1) --> X(0, v, 2) in the secondary reaction product C(2)H, whose formation route is favoured by the presence of buffer gas.